SERANGAN HAMA PUTIH PALSU Cnaphalocrosis medinalis GUENEE. PADA TANAMAN PADI SAWAH DI KECAMATAN RANOYAPO KABUPATEN MINAHASA SELATAN - Vera E. Tangkilisan; Christina L. Salaki; Moulwy F. Dien; Elisabet R.M. Meray (Universitas Sam Ratulangi, 2014)
ABSTRACTThe study aims to determine the pest Cnaphalocrosis medinalis on rice crops in the vegetative phase Ranoyapo districts, South Minahasa Regency. The study uses a survey method in 4 locations / villages in the district Ranoyapo: Ranoyapo Village, West PoopoVillage, North Poopo Village, and MopoloVillage. Each location/village rice fields specified 3 (replicates) as the observation and sampling. Sampling was conducted on each diagonal fields. In each sub-plot clumps of rice as determined 5 sampling sites. Implementation of sampling vegetative phase in rice plants once a week for 6 weeks. The results showed that C. medinalis Ranoyapo has spread in the district with the highest attack found in Ranoyapo village location reached 18.66 %, after reaching West Poopo 8.07%, North Poopo reached 4.29% and Mopolo reached 4.07 %. C. medinalis highest percentage of attacks found in plants aged 6 weeks after planting (mst) which reached 20.66 % , then 5 mst old plants reached 13.55 % , 4 mst old plants reached 10.88 % , and the plant was 3 mst reached 7.55% , while the old plants 1 and 2 mst not encountered attacks. The highest population of C. medinalis found in location for Ranoyapo village reaching an average of 12.7 tail , then the village of West Poopo 4.3 tails , North Poopo Village 3.5 tail , and the tail 3.2 Mopolo village.Key words : Cnaphalocrosis medinalis, Rice field